2017
DOI: 10.1016/j.jad.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Using the NANA toolkit at home to predict older adults’ future depression

Abstract: We have identified self-reported scales of sadness and tiredness as sensitive measures which have the potential to predict future depression status in older adults, partially addressing the problem of underdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Measuring mood and appetite [19][20][21][22] was recently used for predicting depression and anxiety in older adults. These, together with other studies highlighted in our literature, have motivated us to develop our autonomous remote monitoring and decision support tool further and to employ various machine learning approaches including deep learning, while this was previously considered impossible due to big data issues [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring mood and appetite [19][20][21][22] was recently used for predicting depression and anxiety in older adults. These, together with other studies highlighted in our literature, have motivated us to develop our autonomous remote monitoring and decision support tool further and to employ various machine learning approaches including deep learning, while this was previously considered impossible due to big data issues [8].…”
Section: Resultsmentioning
confidence: 99%
“…Computer Interactive Reminiscence and Conversation Aid (CIRCA) has been adopted and developed for cognitive stimulation therapy (CST) by various authors [16][17][18]. NANA (Novel Assessment of Nutrition and Ageing) was developed as a mean for computerized self-administered measures of mood and appetite [19][20][21][22] and was recently used for predicting depression and anxiety in older adults [21,22]. Subramaniam and Woods [23] presented original works on ICT reminiscence systems for dementia with a therapeutic view.…”
Section: Ict For MCImentioning
confidence: 99%
“…The first category includes six articles, focusing on outcomes relating to post-surgical limitations or improvements, such as quality of life after cancer surgery [21] and (walking) limitations or improvements (minimal clinically important difference (MCID)) after total joint arthroplasty [22][23][24][25][26]. The second category includes four articles, focusing on identifying patients with depression based on self-reports [18,27] and prognosis of outcome of anti-depression treatment [28,29]. The third category includes three articles focusing on predicting pain volatility amongst users of a pain-management mobile application [30,31] and self-referral decision support for patients with low back pain in primary care [32].…”
Section: Intervention Domains and Length Of Predictionmentioning
confidence: 99%
“…Currently, PROMs data are widely used in explanatory research, where researchers typically test hypotheses using a preconceived theoretical construct by applying statistical methods (for example, low back pain is associated to lower quality of life and depression [16,17]. In contrast, PROMs in predictive research can be used to predict outcomes in the future by applying statistical or machine learning methods without any preconceived theoretical constructs (for example, predicting the risk of depression [18]), and is therefore an important step towards patient-centred care with a shift in focus towards the patient's perspective [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, negative affect was found to be predictive of depression onset in youth [62]. There are a very limited number of prognostic studies available, focusing on older adults [63]. Authors have identified the items "sad" and "tired" as sensitive measures that have the potential to predict future depression status in older adults.…”
Section: Comparison With Prior Workmentioning
confidence: 99%